Effects of COMT polymorphism on the cortical processing of vocal pitch regulation. Issue 18 (12th December 2018) - Zhang, Siyun; Wang, Wenda; Zhang, Baofeng; Liu, Peng; Liu, Hanjun
Abstract : Recent evidence has shown that auditory-motor integration for speech production is influenced by cognitive functions such as working memory and attention, suggesting that speech motor control is likely modulated by mechanisms mediated by prefrontal regions. Catechol- O -methyltransferase ( COMT ) gene plays an important role in dopamine breakdown in the prefrontal cortex and has been associated with a variety of prefrontal cognitive functions. The present event-related potential study investigated the association between COMT Val 158 Met polymorphism and auditory-motor processing of vocal feedback errors. A sample of 131 Chinese young female adults was genotyped for rs4680 and produced sustained vowels while hearing their voice unexpectedly shifted down in pitch by 50 or 200 cents. The behavioral results showed no effects of COMT Val 158 Met on vocal compensations for pitch perturbations. However, individuals with the Met allele produced significantly larger P2 responses to −200 cents perturbations than individuals with the Val/Val genotype. These results suggest the existence of a relationship between COMT Val 158 Met polymorphism and self-monitoring of speech feedback errors, and they provide insights into our understanding of the top-down modulations of speech motor control mediated by prefrontal regions.